2017
DOI: 10.1021/acs.est.7b02884
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Magnetic Nanoparticle-Decorated Nanofiber Filter and Its Applications to High-Efficiency Air Filtration

Abstract: Filtration technology has been widely studied due to concerns about exposure to airborne dust, including metal oxide nanoparticles, which cause serious health problems. The aim of these studies has been to develop mechanisms for the continuous and efficient removal of metal oxide dusts. In this study, we introduce a novel air filtration system based on the magnetic attraction force. The filtration system is composed of a magnetic nanoparticle (MNP)-decorated nanofiber (MNP-NF) filter. Using a simple electrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 39 publications
(56 reference statements)
0
58
0
Order By: Relevance
“…In addition to making a long-surviving electret, magnetic force was used by incorporating magnetic particles in fibers [ 66 , 67 , 68 ]. In a study by Kim et al [ 69 ], poly(vinylpyrrolidone) (PVP) was electrospun, dispersing Fe 3 O 4 magnetic nanoparticles in the pre-spinning solution. When the produced web was magnetized by an external magnetic field, the collection efficiency of metal oxide particles (Fe 2 O 3 ), one of the major components of subway dust, was greatly enhanced [ 69 ].…”
Section: Materials For Superior Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to making a long-surviving electret, magnetic force was used by incorporating magnetic particles in fibers [ 66 , 67 , 68 ]. In a study by Kim et al [ 69 ], poly(vinylpyrrolidone) (PVP) was electrospun, dispersing Fe 3 O 4 magnetic nanoparticles in the pre-spinning solution. When the produced web was magnetized by an external magnetic field, the collection efficiency of metal oxide particles (Fe 2 O 3 ), one of the major components of subway dust, was greatly enhanced [ 69 ].…”
Section: Materials For Superior Filtrationmentioning
confidence: 99%
“…In a study by Kim et al [ 69 ], poly(vinylpyrrolidone) (PVP) was electrospun, dispersing Fe 3 O 4 magnetic nanoparticles in the pre-spinning solution. When the produced web was magnetized by an external magnetic field, the collection efficiency of metal oxide particles (Fe 2 O 3 ), one of the major components of subway dust, was greatly enhanced [ 69 ]. Zhao et al [ 54 ] incorporated various kinds of negative ions including Al 2 O 3 , SiO 2 , MgO, Fe 2 O 3 , Na 2 O, TiO 2 , and FeO into the PVDF electrospun fibers.…”
Section: Materials For Superior Filtrationmentioning
confidence: 99%
“…Notably, the M S values for the electrospun PVB/MNPs membranes produced herein exceeded those of similar magnetic membranes reported in the literature. [8,26,[35][36][37] At this point, it should be noted that the concentration of each component related to the feedstock solution prior to commencement of the electrospinning process. Assuming absolute evaporation of methanol takes place during the process at both the polymer jet and target collector, the true content of the magnetic filler (MF) can be determined by the following equation: where M S (membrane) and M S (MNPs) are the saturation magnetizations of the membrane and neat MNPs, respectively.…”
Section: Magnetic Properties Of the Membranesmentioning
confidence: 99%
“…40 The researches have shown that the instantaneous high pressure would generate when the PM in the air was close to the magnetic air filter, which enhances the electrostatic adsorption and traction of fabric to PM and results in the higher filtration efficiency. 44,45 Besides, the magnetic air filters can effectively filter metallic oxide dust in the air, which also could improve the filtration efficiency. 44 However, when the Fe 3 O 4 -g-PLLA content continued to increase, the filtration efficiency of the composite MB started to decline and even slightly lower than that of pure PLA MB when Fe 3 O 4 -g-PLLA content was 2 wt%.…”
Section: The Geometric Structures and Filtration Performances Of The mentioning
confidence: 99%
“…44 At present, it has been found that once the air filter is endowed with magnetism, its filtration performances should be enhanced because the presence of magnetism increases the attraction and collection capacities of the filter to the dust. 44,45 Ferroferric oxide (Fe 3 O 4 ) is a kind of magnetic inorganic nanoparticle and has aroused many scholars' interest on account of its advantages, such as superior magnetic responsiveness, nontoxic and inexpensive. 46 Blending PLA with Fe 3 O 4 nanoparticles is a feasible way to make PLA MB obtain the magnetism.…”
Section: Introductionmentioning
confidence: 99%